Molecular Diagnosis of TB in the HIV Positive Population - Amy Y. Vittor; Joseph M. Garland; Robert H. Gilman (Ubiquity Press, 2015)
Background: Tuberculosis (TB) remains a major contributor to morbidity and mortality in HIV-positive individuals, causing 1.1 million incident cases and 0.32 million deaths in 2012. Diagnosis of TB is particularly challenging in HIV-coinfected individuals, due to a high frequency of smear-negative disease, atypical presentations, and extrapulmonary TB. Objective: The aim of this article was to review the current literature on molecular diagnostics for TB with an emphasis on the performance of these diagnostic tests in the HIV-positive population. Methods: We searched the PubMed database using at least one of the terms TB, HIV, diagnostics, Xpert MTB/RIF, 'nucleic acid amplification tests', drug susceptibility testing, RNA transcription, and drew on World Health Organization publications. Findings: With increased focus on reducing TB prevalence worldwide, a new set of tools for diagnosing the disease have emerged. Molecular tools such as Xpert MTB/RIF and line-probe assays are now in use or are being rolled out in many regions. The diagnostic performance of these and other molecular assays are discussed here as they pertain to the HIV-positive population. Conclusions Molecular diagnostics offer a useful addition and at times, alternative, to traditional culture methods for the diagnosis of TB. However, most of these tests suffer from decreased accuracy in the HIV-positive population.